Dari Nature Tourism ke Ecotourism: Menakar Keterpenuhan Prinsip-Prinsip Ecotourism pada Kawasan Wisata Alam di Bangka Belitung: From Nature Tourism to Ecotourism: Assessing the Ecotourism Principles Fulfillment of Tourism Natural Areas in Bangka Belitung - Ibrahim Ibrahim; Nizwan Zukhri; Rendy Rendy (Society, 2019)
Bangka Belitung is being transformed into a tourism destination area, relying on nature tourism. But unfortunately, the development of nature tourism does not include the development of ecotourism, even though these two things are interrelated. Nature tourism which is a mainstay of the tourism sector provides a very wide opportunity to strengthen ecotourism as part of the environmental movement in Bangka Belitung. This research aims to find out how the fulfillment of the ecotourism principles of tourism natural areas in Bangka Belitung Islands Province, Indonesia, and identifying unique things related to the application of these principles. Through quantitative research methods with a survey approach that is strengthened by field observations, this research found that assessed from 5 interval categories of the ecotourism principles fulfillment, 58% of the tourism areas in Bangka Belitung were included in the category of fulfilled of the ecotourism principles and 42% were in the strongly fulfilled category of the ecotourism principles. The research also found that although the application of each principle was met, there were unique and interesting notes on each principle.